(3GdEOGQI GdeGdjI aj Jehjd GdTQcGJ eJYOOI GdLfSjGJs - (3YHO GdYRjR eMeO(B, (3GdfLGQs ((3GdGScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2007)
(3GdeONd Edi OQGSI GdTQcGJ eJYOOI GdLfSjI,EWGQ eaGgjej ddTQcI eJYOOI GdLfSjI,GdfhGMj GdJfXjejI ddEOGQI GdeGdjI aj GdTQcI GdeJYOOI GdLfSjI,GdOhQ GdJehjdj ddTQcGJ eJYOOI GdLfSjI aj GdJfejI aj GdOhd GdfGejI GdeVjaI,Gdehba ef GdTQcGJ eJYOOI GdLfSjI aj GdacQ GdJfehj,OGaYjI GdTQcI eJYOOI GdLfSjI cOGdI dESJQGJjLjI GdESJKeGQ aj GdTQcI eJYOOI GdLfSjI,GdefGN GdESJKeGQj ddTQcI eJYOOI GdLfSjIs
Keywords: (3GdEOGQI GdeGdjIs; (3GdTQcGJ GdCLfHjIs; (3GdTQcGJ(B-(3Jehjds